ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DALAM MENYELESAIKAN SOAL CERITA MATERI PERSAMAAN LINEAR SATU VARIABEL PADA SISWA SMP - Eriska Sonia; Adi Nurjaman; Masta Hutajulu (IKIP Siliwangi, 2022)
The ability to solve problems is one of the abilities that students need to have in learning mathematics. Especially solving stories or non-routine questions, students really need to have the ability to solve these problems. Therefore, this study aims to determine and examine the ability to solve mathematical problems in solving one-variable linear equation (PLSV) material stories in junior high school students conducted in one of the public junior high schools in the city of Cimahi. This research method uses a qualitative descriptive method. The subjects of this study were 15 grade VII junior high school students and the data obtained by testing 4 written tests in the form of stories related to everyday life which refers to the steps of problem solving skills, namely finding mathematics from data, making mathematical models from problems. story, planning a settlement strategy, checking the correctness of the answer. From the results of research that has been done that the problem-solving ability of students is still relatively low because students are not accustomed to working on the form of story questions which causes students to find it difficult to determine the steps to be able to solve problems, formulate story questions into mathematical models.